2019
DOI: 10.1149/2.0091901jss
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Electrical and Interfacial Properties of Improved Ohmic Contact on p-Type GaN

Abstract: Ohmic contacts on p-GaN with Pd/Pt/Au metallization scheme deposited at room temperature and elevated temperature were prepared to study the effect of metal deposition temperature on the contact properties. The specific contact resistance decreased by the heat-treatment of the p-GaN sample in an ultra-high vacuum environment. The in-diffusion of Au atoms and out-diffusion of Pd atoms are further suppressed by the diffusion barrier layer deposited at elevated temperature. The interfacial microstructure shows th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…However, once undergoing a high‐temperature annealing process, Au atoms could inevitably diffuse into the contact metal layer through some defects and grain boundaries populating the metal stacks. In our earlier results, [ 26 ] we found that a diffusion barrier deposited at an elevated temperature more effectively suppresses the indiffusion of Au atoms and outdiffusion of Pd atoms, which promotes the Ohmic contact characteristics. In addition to deposition temperature, we also noted that carbon and oxygen contaminants have a significant effect on Au indiffusion behaviors and contact resistance.…”
Section: Resultsmentioning
confidence: 65%
“…However, once undergoing a high‐temperature annealing process, Au atoms could inevitably diffuse into the contact metal layer through some defects and grain boundaries populating the metal stacks. In our earlier results, [ 26 ] we found that a diffusion barrier deposited at an elevated temperature more effectively suppresses the indiffusion of Au atoms and outdiffusion of Pd atoms, which promotes the Ohmic contact characteristics. In addition to deposition temperature, we also noted that carbon and oxygen contaminants have a significant effect on Au indiffusion behaviors and contact resistance.…”
Section: Resultsmentioning
confidence: 65%